2021
DOI: 10.1007/jhep03(2021)235
|View full text |Cite
|
Sign up to set email alerts
|

Bottomonium suppression and elliptic flow using Heavy Quarkonium Quantum Dynamics

Abstract: We introduce a framework called Heavy Quarkonium Quantum Dynamics (HQQD) which can be used to compute the dynamical suppression of heavy quarkonia propagating in the quark-gluon plasma using real-time in-medium quantum evolution. Using HQQD we compute large sets of real-time solutions to the Schrödinger equation using a realistic in-medium complex-valued potential. We sample 2 million quarkonia wave packet trajectories and evolve them through the QGP using HQQD to obtain their survival probabilities. The compu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 81 publications
1
19
0
Order By: Relevance
“…We found that our results for transverse-momentum dependence of bottomonia elliptic flow are in good agreement with experimental results from the ALICE and CMS collaborations. They also agree with recent calculations [55,56] simulating the real time quantum evolution of bottomonium states in the QGP, relaxing the assumption of an adiabatic evolution of the bb system [57]. Looking forward, one can anticipate greatly increased statistics in future runs from the experimental collaborations at LHC.…”
Section: Discussionsupporting
confidence: 84%
“…We found that our results for transverse-momentum dependence of bottomonia elliptic flow are in good agreement with experimental results from the ALICE and CMS collaborations. They also agree with recent calculations [55,56] simulating the real time quantum evolution of bottomonium states in the QGP, relaxing the assumption of an adiabatic evolution of the bb system [57]. Looking forward, one can anticipate greatly increased statistics in future runs from the experimental collaborations at LHC.…”
Section: Discussionsupporting
confidence: 84%
“…Here, we follow refs. [15,16] and introduce a feed down matrix F which collects the known information about excited bottomonium state decays available from the Particle Data Group [94].…”
Section: Final Results Including Late-time Feed Down Of Excited Statesmentioning
confidence: 99%
“…The imaginary part also leads to quarkonium dissociation, which turns out to happen at a temperature lower than the screening one [3][4][5][6], i.e., at least in weak coupling, quarkonium has already dissociated when reaching the screening temperature. Since then, many phenomenological studies solving the Schrödinger equation with a complex potential have appeared [7][8][9][10][11][12][13][14][15][16].…”
Section: Jhep05(2021)136mentioning
confidence: 99%
“…Even prior to this manuscript the results of this tuning have been used, e.g. to study the nuclear modification factor R A A and elliptic flow v 2 of bottomonium states in 5.02 TeV Pb-Pb collisions [54,55].…”
Section: Introductionmentioning
confidence: 99%